WHAT AND HOW SHOULD THE PUBLIC SPEAKING BE? : A LITERATURE REVIEW - Dirgayasa, I Wayan (Journal of Language, Literature and Teaching, 2023)
Public speaking is a kind of or a part of art of delivering speech in front of the audiences. It is also the art of communication science effectively and properly. However, in many social circumstances and contexts of public speaking, many speakers still seemingly anxious and cannot effectively and properly deliver their speech. This may happen due to some reasons such as unfamiliar with the topic, the background of the audience, lack of language mastery (for example English), the ways and norm, and rules as well to speak in public. This paper attempt to mainly discusses about the nature of public speaking, the common types of public speaking, factors affecting the public speaking, and public speaking in a multilingual world.Key words: public speaking, types of public speaking, factors affecting public speaking, and multilingual world.